Level of Taxpayer Trust in Tax Officials (Study on Taxpayers in Bekasi City) - Sihite, Putriani Magdalena; Riyanto, Didik; Abdillah, Abdillah (Mahameru Publisher, 2023)
This study aims to understand the perception of the level of trust of taxpayers towards tax officials. This type of research is descriptive quantitative with research data obtained directly from respondents' answers to questionnaires. The population in this study is individual taxpayers registered in Bekasi city. The sampling technique used in this study is a simple random sampling technique. The results showed that the perception of the level of trust in the character of tax officials states that taxpayers believe in the character of tax officials which includes attitude, personality and integrity. Then the perception of the level of trust in the performance of tax officials which includes leadership, discipline and competence of tax officials where taxpayers lack confidence in the performance of tax officials. Therefore, the perception of the level of taxpayer trust in tax officials from the overall survey results which include character and performance states that taxpayers lack trust even though the results of the survey trust in the character of taxpayers trust but are very close to less trust.